2004
DOI: 10.1007/s00438-004-0992-x
|View full text |Cite
|
Sign up to set email alerts
|

Sinorhizobium meliloti RpoH1 is required for effective nitrogen-fixing symbiosis with alfalfa

Abstract: Sinorhizobium meliloti is a root-nodulating, nitrogen-fixing bacterium. An S. meliloti strain that is mutant for the rpoH(1) gene, which encodes a sigma(32)-like protein, elicits the formation of ineffective nodules on the host plant alfalfa. We characterized the rpoH(1) mutant for phenotypes related to symbiosis. Alfalfa nodules formed by the rpoH(1) mutant exhibited greatly reduced levels of acetylene reduction activity compared to the wild-type nodules. Whereas intracellular colonization by rhizobia was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
88
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(107 citation statements)
references
References 35 publications
17
88
1
1
Order By: Relevance
“…These data suggest that, even at sublethal levels, NCR247-peptide treatment activates a cytoplasmic stress response in S. meliloti cells. This finding is particularly intriguing because it could explain why S. meliloti rpoH1 mutants die soon after being internalized within plant cells that express NCR peptides (27,28). Collectively, our data strongly suggest that cationic NCR peptides exert their effects by targeting the S. meliloti cell envelope, periplasm, and cytoplasm and suggest mechanisms through which S. meliloti adapts to NCR peptide-mediated stress in vitro and during symbiosis.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…These data suggest that, even at sublethal levels, NCR247-peptide treatment activates a cytoplasmic stress response in S. meliloti cells. This finding is particularly intriguing because it could explain why S. meliloti rpoH1 mutants die soon after being internalized within plant cells that express NCR peptides (27,28). Collectively, our data strongly suggest that cationic NCR peptides exert their effects by targeting the S. meliloti cell envelope, periplasm, and cytoplasm and suggest mechanisms through which S. meliloti adapts to NCR peptide-mediated stress in vitro and during symbiosis.…”
Section: Discussionmentioning
confidence: 68%
“…Genes specifically induced by NCR247 include genes involved in glycogen metabolism (glgA1, glgC, and glgX1), potassium transport (kdpA-C), global stress responses (fecI and rpoH1), and hypothetical genes. The effect on rpoH1 expression is particularly notable, because RpoH1 is required for bacteroid differentiation and survival in host legumes that produce cationic NCR peptides (27,28). RpoH1 regulates a suite of genes during heat and pH stress (29, 30), and we found that a subset of RpoH1-dependent genes was induced in NCR247-treated cells (Dataset S1).…”
Section: Ncr247-peptide Treatment Affects the Expression Of Genes Andmentioning
confidence: 88%
“…Mutants that are defective in global bacterial transcriptional responses under stress conditions are also defective in symbiosis. A mutant in rpoH1, encoding a putative σ 32 -factor that is predicted to interact with bacterial RNA polymerase, appears to invade normally, but forms bacteroids that senesce prematurely 86 . By contrast, a mutant in relA is defective at multiple stages in nodule formation 87 ; relA mutants lack the stringent response -a bacterial transcriptional response to starvation 87 .…”
Section: Box 3 Host Invasion Parallels Between Rhizobia and Animal Pamentioning
confidence: 99%
“…One possibility is that the genes may be differentially regulated to provide GroEL/GroES at different times or at different levels. Such regulation has been observed in a number of species (5,12,16,25,26,30,41). A second possibility is that the genes may encode proteins with different substrate specificities.…”
mentioning
confidence: 96%
“…All of the single S. meliloti groEL mutants are viable (5,30,34,35), but groEL1 and groEL2 cannot be disrupted at the same time (34). The effect of groE mutations on growth rate has been determined only for the groEL1 mutant, which has a longer doubling time at 30°C than the wild type (27,35).…”
mentioning
confidence: 99%